Pathogenic old world hantaviruses infect renal glomerular and tubular cells and induce disassembling of cell-to-cell contacts - Krautkrämer, Ellen; Grouls, Stephan; Stein, Nadine; Reiser, Jochen; Zeier, Martin (Journal of virology, 2011)
Viral hemorrhagic fevers are characterized by enhanced permeability. One of the most affected target organs of hantavirus-induced hemorrhagic fever with renal syndrome is the kidney, and an infection often results in acute renal failure. To study the underlying cellular effects leading to kidney dysfunction, we infected human renal cell types in vitro that are critical for the barrier functions of the kidney, and we examined kidney biopsy specimens obtained from hantavirus-infected patients. We analyzed the infection and pathogenic effects in tubular epithelial and glomerular endothelial renal cells and in podocytes. Both epithelial and endothelial cells and podocytes were susceptible to hantavirus infection in vitro. The infection disturbed the structure and integrity of cell-to-cell contacts, as demonstrated by redistribution and reduction of the tight junction protein ZO-1 and the decrease in the transepithelial resistance in infected epithelial monolayers. An analysis of renal biopsy specimens from hantavirus-infected patients revealed that the expression and the localization of the tight junction protein ZO-1 were altered compared to renal biopsy specimens from noninfected individuals. Both tubular and glomerular cells were affected by the infection. Furthermore, the decrease in glomerular ZO-1 correlates with disease severity induced by glomerular dysfunction. The finding that different renal cell types are susceptible to hantaviral infection and the fact that infection results in the breakdown of cell-to-cell contacts provide useful insights in hantaviral pathogenesis.